Kajian Fraud Hexagon dalam Mendeteksi Fraudulent Financial Reporting pada Perusahaan Manufaktur Sektor Makanan dan Minuman di BEI (2020-2022) - Susanto, Endrico; Triyani, Yustina (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2025)
This study aims to determine the effect of fraud hexagon on fraudulent financial reporting. The sample of this study were 52 food and beverage sector manufacturing companies listed on the Indonesia Stock Exchange during the period 2020 - 2022. The sampling technique used was non-problability sampling technique using purposive sampling method and data testing was carried out using SPSS 25. The data analysis techniques used include descriptive statistical analysis, pooling test, classical assumption test, and hypothesis testing. The results showed that the total accrual ratio had a positive effect on fraudulent financial reporting, while financial targets, change in director, political connection, ineffective monitoring and CEO duality had no effect on fraudulent financial reporting.